Pengenalan Olahraga Squash Sebagai Media Interaktif Menggunakan Teknologi Augmented Reality (AR) Berbasis Android - Andana Maulana Munggaran; Siti Sundari (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
This research discusses the design and development of an interactive media application based on Augmented Reality (AR) technology to introduce the sport of squash to students. The developed Android-based application is capable of displaying 3D objects of squash equipment and basic techniques through predetermined markers. In addition to interactive visualization, this media is also equipped with supporting information, educational quizzes, and explanatory audio to enrich the user’s learning experience. The implementation results show that the use of Augmented Reality technology can enhance the understanding of squash in a more realistic and comprehensive way. The 3D visualization displayed through the camera provides a direct representation of squash techniques, while the interactivity in the form of descriptive texts and supporting audio makes the learning process more engaging, easier to understand, and able to foster students’ interest in the subject matter. Based on testing and questionnaire distribution, the application received positive feedback from users. A total of 94.44% of respondents gave positive assessments of the developed learning media, 5.56% responded neutrally, and none responded negatively. Thus, it can be concluded that AR-based learning media has been successfully designed and implemented as an effective and interactive tool, capable of improving learning motivation and providing a more attractive learning experience in understanding squash.